Dementia diagnosis and post-diagnostic support in Scottish rural communities: Experiences of people with dementia and their families. (March 2014) - Innes, Anthea; Szymczynska, Paulina; Stark, Cameron
This paper explores the reported difficulties and satisfactions with diagnostic processes and post-diagnostic support offered to people with dementia and their families living in the largest remote and rural region in Scotland. A consultation with 18 participants, six people with dementia and 12 family members, was held using semi-structured interviews between September and November 2010. Three points in the diagnostic process were explored: events and experiences pre-diagnosis; the experience of the diagnostic process; and post-diagnostic support. Experiences of people with dementia and their carers varied at all three points in the diagnostic process. Participant experiences in this study suggest greater efforts are required to meet Government diagnosis targets and that post-diagnostic support needs to be developed and monitored to ensure that once a diagnosis is given people are well-supported. Without post-diagnostic provision Government targets for diagnosis are just that, quota targets, rather than a means to improve service experiences.